Pengaruh Net Profit Margin, Return On Equity, Return On Asset, dan Current Ratio terhadap Harga Saham Pada Perusahaan Manufaktur Sektor Industri Barang dan Konsumsi Yang Listing di Bursa Efek Indonesia Pada Tahun 2018 - 2021 - Rusmana, Haris; Yuliani, Rahma (Department of Accounting, Faculty of Economics & Business, 2024)
This research was conducted to prove and analyze (1) the effect of Net Profit Margin on stock prices, (2) The effect of Return On Equity on Stock Prices (3) the effect of Return On Assets on stock prices (4) and the effect of Current Ratio on stock prices. The population in this study are manufacturing companies in the goods and consumption sector which are listed on the Indonesia Stock Exchange from 2018-2021, totaling 111 companies. The sample in this study consisted of 25 companies. The type of data in this study is secondary data obtained by collecting document/copy archival data through the Indonesian Stock Exchange website. This type of research is quantitative research. The analysis technique used in this study was multiple regression analysis using the IBM SPSS Statistics application version 25. The results of this study indicate that the Net Profit Margin, Return On Equity, Return On Assets, Current Ratio has no significant effect on stock prices. The coefficient of determination is 0.127, which means 12.7%, which means that the stock price is affected by 12.7% by Net Profit Margin, Return On Equity, Return On Assets, Current Ratio, while the rest is explained by other variables. This shows that there are variables outside the research that can affect stock prices.